Native American Studies Meets Animal Studies: Linda Hogan’s The Radiant Lives of Animals and the Problem of Anthropomorphism - Joanna Ziarkowska (European Journal of American Studies)
The aim of this article is to offer a theoretical framework derived from animal studies to read The Radiant Lives of Animals by Chickasaw writer Linda Hogan. While Hogan’s insights into non-human animals’ lives are sensitive and insightful, they may seem anthropomorphic. To illuminate the rationale behind Hogan’s choice of imagery, I propose to read The Radiant Lives through the work of Vinciane Despret’s concept of anthropo-zoo-genesis. Despret’s concept is relevant for Hogan’s work as she is, in the same way, genuinely interested in the interactions of bodies, the embodied character of life.